O Magnum Mysterium? Eco‐theology at the foot of the Cross. (29th January 2022) - Tyler, Peter
Abstract: In Laudato Si', Pope Francis urges not just a renewal of respect for creation but also a metanoia in our attitude to the created world. This article is a response to the Pontiff's challenge, exploring how a distinctively 'modern' approach to creation arose in the late nineteenth century which still influences our attitudes today. As those attitudes arose, however, the article argues that Christian thinkers were able to articulate other approaches, which are referred to as 'doing eco‐theology at the foot of the Cross'. The article explores these views and their implications in shaping a Christian response to the present ecological crisis within which we find ourselves. In particular, it concentrates on the interpretations of 'nature' in the writings of the German atheist philosopher Friedrich Nietzsche (1844–1900) and his exact English Jesuit contemporary Gerard Manley Hopkins (1844–1889) who were bothworking at the dawn of the 'modern' view of 'nature' and creation.